Microchemical inhomogeneity in eutectic Pb–Bi alloy quenched from melt1. (29th January 2014) - Mezzi, A.; Kaciulis, S.; Balijepalli, S. K.; Montanari, R.; Varone, A.; Amati, M.; Aleman, B.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
ABSTRACT The liquid lead‐bismuth eutectic alloy is of great interest for applications in advanced nuclear systems; in particular, it is considered to be a good candidate as a coolant and neutron spallation source material for MYRRHA (http://myrrha.sckcen.be/), an accelerator driven system. Investigations based on mechanical spectroscopy experiments and high‐temperature X‐ray diffraction evidenced that the structure of the liquid alloy is not stable but undergoes relevant changes as the temperature increases. To understand whether such transformations, occurring in the liquid state involve elemental clustering, the alloy has been water‐quenched from the liquid state at three different temperatures. After quenching, the samples have been investigated by standard XPS and scanning photoemission microscopy at the ELETTRA synchrotron. The SPEM results showed that the distribution of two metals is characterised by the following: (i) Pb‐enriched clusters, (ii) Bi‐enriched clusters and (iii) matrix in near eutectic composition. The statistics of clusters size was evaluated from the linescans of chemical Pb/Bi images. The average size of clusters is noticeably reduced by increasing quenching temperature: it is in the range of 1 ÷ 3 µm at 313 °C and passes to 0.5 ÷ 0.9 µm at 518 °C. Therefore, scanning photoemission microscopy results evidenced a structural and microchemical rearrangement of the atoms in the melt consisting in the evolution of cluster size and composition. Copyright © 2014 John Wiley & Sons, Ltd.